The genus Psilotreta Banks (Trichoptera, Odontoceridae) in Japan - Kawase, Naoki (Zootaxa, 2022)
The Japanese species of Psilotreta Banks (Trichoptera, Odontoceridae) are reviewed. Five described species and three new species are recognized: P. japonica (Banks 1906), P. kisoensis Iwata 1928, P. voluta Kawase 2021, P. moritai Kawase 2021, P. flavida Kawase 2021, P. spatulata sp. nov., P. atrocaudata sp. nov., and P. bitubercula sp. nov. Adults of the three new species are described and those of P. japonica and P. kisoensis are redescribed. Illustrations of male and female genitalia of the remaining three species are provided for comparison. The larva of P. spatulata sp. nov. is described and those of P. japonica and P. kisoensis are redescribed. The larva of P. voluta is indistinguishable from that of P. spatulata sp. nov.